Mechanical property changes of glial LC and RGC axons in response to high intraocular pressure - Bochao Ma; Liu Liu; Liu Liu; Yushu Liu; Yushu Liu; Jifeng Ren; Jifeng Ren; Xiuqing Qian; Xiuqing Qian (Frontiers in Bioengineering and Biotechnology)
IntroductionPathological high intraocular pressure (IOP) is an important risk factor for glaucoma. The lamina cribrosa (LC) area in the optic nerve head is the initial site of optic nerve injury for glaucoma. LC deformation caused by elevated IOP will compress the retinal ganglion cells (RGC) axons passing through it, thereby leading to the damage of the RGC axons. The deformation of LC is highly correlated with its mechanical properties. Therefore, changes in mechanical properties of LC with the duration of high IOP is of great significance.MethodsTo investigate the impact of chronic high IOP on the mechanical properties of the LC, rat models were established by cauterizing the superior scleral vein and injecting 5-fluorouracil (5-FU) under the conjunctiva to maintain elevated IOP. The linear elastic properties of the glial LC and RGC axons in affected eyes were measured using atomic force microscopy (AFM) combined with image segmentation techniques. Morphological alterations of the glial LC were assessed using hematoxylin-eosin staining, immunofluorescence staining, and transmission electron microscopy (TEM).ResultsCompared to the control group, the Young's modulus of the glial LC decreased by 35.5%, 74.2%, and 80.6% at 4, 8, and 12 weeks of elevated IOP, respectively. Similarly, the Young's modulus of RGC axons decreased by 45.6%, 70.9%, and 75.9% over the same time points. These findings demonstrate a time-dependent reduction in the mechanical stiffness of both glial LC and RGC axons under chronic high IOP conditions.DiscussionThe progressive decrease in Young's modulus indicated that prolonged high IOP compromises the structural integrity and mechanical properties of the LC and RGC axons. This mechanical weakening likely contributes to the pathophysiological process of optic nerve injury in glaucoma. The present study offers important insights into the biomechanical mechanisms underlying glaucomatous damage, which may guide future research and therapeutic strategies.